Good vision without peripheries: behavioral and fMRI evidence - M. Ninghetto; A. Kozak; T. Gałecki; K. Szulborski; J. P. Szaflik; M. Ołdak; A. Marchewka; K. Burnat (Scientific Reports)
Abstract In healthy vision, bright slow-motion stimuli are processed primarily by the regions of the visual system that receive input from the central part of the scene, whereas processing of dark fast-motion stimuli is more dependent on peripheral visual input. We tested 31 retinitis pigmentosa (RP) patients with long-term loss of peripheral photoreceptors and healthy controls with temporarily limited peripheral vision. We measured motion-based acuity using random-dot kinematograms, establishing individual thresholds for differentiating a circle from an ellipse. Participants subsequently performed a functional magnetic resonance imaging (fMRI) task set at a constant level of difficulty. The results showed that limiting vision did not affect motion-acuity thresholds in control participants but did cause different brain activations than those in RP patients, indicating prompt implementation of the strategy that would be perceptually successful. Compared with controls with both full and limited vision, impaired motion acuity in RP patients led to decreased brain activation, particularly in the primary peripheral visual areas V1-3. Importantly, compared with controls in full vision, matched decreased activation in MT+/V5, salience-processing cortices and the superior temporal cortex were detected in RP patients and in controls with limited peripheral vision, revealing brain networks that compensate for the loss of peripheral vision.